2017
DOI: 10.5090/kjtcs.2017.50.3.211
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Repair of Ventricular Septal Rupture Following Preoperative Awake Extracorporeal Membrane Oxygenation Support

Abstract: Outcomes of ventricular septal rupture (VSR) as a complication of acute myocardial infarction are extremely poor, with an in-hospital mortality rate of 45% in surgically treated patients and 90% in patients managed with medication. Delaying surgery for VSR is a strategy for reducing mortality. However, hemodynamic instability is the main problem with this strategy. In the present case, venoarterial extracorporeal membrane oxygenation (ECMO) was used to provide stable hemodynamic support before the delayed surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 6 publications
(7 reference statements)
0
8
0
Order By: Relevance
“…Several authors have suggested a potential role of ST-VAD use in critical patients with PIVSR during recent years. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Mechanical support may help patients to overcome multiorgan failure and systemic inflammatory response syndrome after a major surgical procedure in unstable conditions. 9,11,13 On the other hand, an early preoperative mechanical support may improve haemodynamic and metabolic status and allow a delayed surgery in a better condition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several authors have suggested a potential role of ST-VAD use in critical patients with PIVSR during recent years. [7][8][9][10][11][12][13][14][15][16][17][18][19][20] Mechanical support may help patients to overcome multiorgan failure and systemic inflammatory response syndrome after a major surgical procedure in unstable conditions. 9,11,13 On the other hand, an early preoperative mechanical support may improve haemodynamic and metabolic status and allow a delayed surgery in a better condition.…”
Section: Discussionmentioning
confidence: 99%
“…9,11,13 On the other hand, an early preoperative mechanical support may improve haemodynamic and metabolic status and allow a delayed surgery in a better condition. 7,8,10,[14][15][16][18][19][20] This approach was assessed in an interesting paper by Rob et al 20 The authors described a series of 31 consecutive patients with PIVSR, of whom 14 were in cardiogenic shock. Half of these cardiogenic shock patients (7/14) underwent femoral VA-ECMO support at admission in order to optimize haemodynamic status and perform scheduled surgery a few days afterwards.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the purpose of maintaining a favorable hemodynamic condition until VSR closure, intra-aortic balloon pumping is usually considered as routine care for mechanical afterload reduction and augmentation of the cardiac output. On the other hand, there have been several reports on the use of ECMO systems to stabilize hemodynamics in this situation until surgery, but the effect of this strategy remains controversial [ 6 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…ECLS, which provides full cardiorespiratory support during this time period, might protect the patient's circulation while allowing time from infarction to the surgical correction, improving surgical outcomes. 226,227 Experience in this area is still anecdotal, but the usefulness of ECLS in these circumstances, i.e. providing temporary support both preoperatively and postoperatively, to counteract RV/LV dysfunction refractory to pharmacological and IABP treatment, has significant appeal.…”
Section: Preoperative Extracorporeal Life Supportmentioning
confidence: 99%